THE USE OF PHOTOGRAPH AS A VISUAL AID IN TEACHING REPORT TEXT WRITING - Sari, Juwita Purnama (2016)
This study was conducted to explore the use of photograph as a visual aid by the teacher in teaching report text writing. This study was a descriptive qualitative case study. The participants of this study were an English teacher as the main participant of this study and a ninth grade class of one of Junior High School in Bandung consisted of 35 students. The data were obtained from classroom observation and interview. The overall findings revealed the whole process of the use of photograph as a visual aid by the teacher from the consideration in designing the lesson plan, selecting the photographs, the findings in classroom observation and interview. Furthermore, this research also showed several findings, those arethe use of photograph helps the teacher in delivering the material, the use of photograph can connect the students with their experience in their own environment, and for the students, the use of photograph can create enthusiasm to the lesson.; Penelitian ini dilakukan untuk mengeskplore penggunaan fotograf sebagai media visual oleh guru dalam mengajar menulis teks report. Penelitian ini merupakan penelitian kualitatif studi kasus yang dijabarkan secara deskriptif. Partisipan yang berkontribusi diantaranya adalah guru bahasa Inggris sebagai subjek utama and 35 murid di kelas sembilan di sebuah SMP di Bandung. Selanjutnya, pengumpulan data dilakukan melalui teknik observasi kelas dan wawancara. Demikian, penemuan di penelitian ini melingkupi seluruh proses dari penggunaan fotograf sebagai media visual oleh guru, mulai dari pertimbangan dalam menyusun RPP, pemilihan fotograf, dan penemuan dalam observasi kelas dan wawancara. Selanjutnya, terdapat beberapa kesimpulan yang didapat, diantaranya adalah penggunaan fotograf membantu guru dalam menyampaikan materi pelajaran, penggunaan fotogtraf dapat menghubungkan materi yang disampaikan dengan pengalaman siswa dalam lingkungan mereka, dan bagi siswa penggunaan fotograf dapat menimbulkan semangat dalam belajar.